Organization of pharmaceutical provision of patients with pulmonary hypertension on the example of Kyiv - I. S. Datsenko; A. V. Kabachna; V. S. Hulpa (The State Expert Center of the Ministry of Health of Ukraine, 2022)
In Ukraine, pharmaceutical provision of patients with pulmonary hypertension (PH) as a rare (orphan) disease is one of the important components of the State policy. Despite the permanent reform of the medical and pharmaceutical sector, a significant number of problems in the formation of a balanced system for providing the necessary medicinal products (MP) to orphan patients have not yet been resolved. The purpose of the study is to study the process of pharmaceutical provision of patients with PH, using the example of Kyiv. Information on MP purchases for patients in Kyiv, included in the Unified Clinical Protocol for Emergency, Primary, Secondary (Specialized) Medical Care Pulmonary Hypertension in Adults for the State and local budgets for 2018-2021, has been chosen as the object of the study. We have used system-review, documentary, and marketing research methods. The result of the analysis of the annual need for 2018-2021 in INN, necessary for the pharmaceutical provision of Kyiv patients with PH, has shown that the annual decrease in funding compared to 2018, namely: in 2019- by 17.54%, in 2020- by 32.52%, in 2021 - by 50.08%, due to a decrease in the cost of INN Sildenafil (Sildenafilum) by an average of 89.21% annually, compared with the cost in 2018. At the same time, the state of providing MP for patients with PH in Kyiv for the period 2018-2021 indicates that the total need for them was met at the expense of the State Budget of Ukraine and the budget of Kyiv for the implementation of the City Target Program «Health of Kievans» in 2018 - by 81.46%, and in 2019 - by 91.67% of the need. The supply of MP ordered for 2020 for the treatment of PH at the expense of the State Budget took place only at the end of 2021. Only Iloprost (Iloprostum) of the six supplies of INN ordered was completed, which accounted for 82.27% of the declared need. In 2021, only Sildenafil (Sildenafilum) was purchased at the expense of the State Budget of Ukraine, which is 8% of the need to provide treatment for patients with PH in the city of Kyiv. The City Target Program «Health of Kievans» for 2021 does not provide for expenses in the «Pulmonary Hypertension» direction. Thus, the results of a study of the organization of pharmaceutical support for Kyiv residents with PH indicate that there are no financial guarantees for the provision of free medical care to patients with rare (orphan) diseases.